Increasing Environmental Awareness in Early Childhood 4-5 Years through the Problem-Based Learning Grophy Garbage Approach - Tazkiya Asti Fatikha; Sri Katoningsih (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
There is an urgent need to instill environmental awareness in early childhood (4-5 years old) at PGRI Jati Kindergarten. The purpose of this study was to test the effectiveness of the Problem-Based Learning (PBL) approach with the "Grophy Garbage" project model in increasing children's environmental awareness. The research method used was a descriptive qualitative approach with a specific study design, involving 15 Group A children at PGRI Jati Kindergarten. This rigorous methodology applies the Kemmis and McTaggart spiral model (planning, implementation, observation, and reflection) to ensure continuous improvement. Data were collected through structured observations of seven indicators of environmental attitudes, in-depth interviews, and documentation. The novelty of this study lies in the integration of the Grophy Garbage project model—which combines visualization of ideas (Grophy) and exploration of used materials (Garbage)—into the Problem Based Learning (PBL) framework in PAUD. This approach is specifically tailored to the characteristics of early childhood, enabling creative expression and contextual learning based on real problems. Research consistently shows that the implementation of Problem-Based Learning (PBL) through "Grophy Garbage" effectively increases environmental awareness in children aged 4-5 years. Children become more enthusiastic and disciplined in disposing of waste, are able to distinguish between types of waste, and are actively involved in making recycled products from plastic bottles, which also improves their fine motor skills. All indicators of environmental awareness, from attention to cleanliness, participation in caring for plants, to collaboration and empathy, show positive developments. The main challenges faced include limited teacher resources and the need for ongoing digital literacy training, but the benefits significantly shape children's ecological character.